Contribution of smoking towards the association between socioeconomic position and dementia: 32-year follow-up of the Whitehall II prospective cohort study - Martina Raggi; Aline Dugravot; Linda Valeri; Marcos D. Machado-Fragua; Julien Dumurgier; Mika Kivimaki; Séverine Sabia; Archana Singh-Manoux (Elsevier, 2022)
Summary: Background: There is consistent evidence of social inequalities in dementia but the mechanisms underlying this association remain unclear. We examined the role of smoking in midlife in socioeconomic differences in dementia at older ages. Methods: Analyses were based on 9951 (67% men) participants, median age 44.3 [IQR=39.6, 50.3] years at baseline in 1985-1988, from the Whitehall II cohort study. Socioeconomic position (SEP) and smoking (smoking status (current, ex-, never-smoker), pack years of smoking, and smoking history score (combining status and pack-years)) were measured at baseline. Counterfactual mediation analysis was used to examine the contribution of smoking to the association between SEP and dementia. Findings: During a median follow-up of 31.6 (IQR 31.1, 32.6) years, 628 participants were diagnosed with dementia and 2110 died. Analyses adjusted for age, sex, ethnicity, education, and SEP showed smokers (hazard ratio [HR] 1.36 [95% CI 1.10-1.68]) but not ex-smokers (HR 0.95 [95% CI 0.79-1.14]) to have a higher risk of dementia compared to never-smokers; similar results for smoking were obtained for pack-years of smoking and smoking history score. Mediation analysis showed low SEP to be associated with higher risk of dementia (HRs between 1.97 and 2.02, depending on the measure of smoking in the model); estimate for the mediation effect was 16% for smoking status (Indirect Effect HR 1.09 [95% CI 1.03-1.15]), 7% for pack-years of smoking (Indirect Effect HR 1.03 [95% CI 1.01-1.06]) and 11% for smoking history score (Indirect Effect HR 1.06 [95% CI 1.02-1.10]). Interpretation: Our findings suggest that part of the social inequalities in dementia is mediated by smoking. Funding: NIH